022. From Challenge to Favorable Outcome: Resection of Progressive and Regrowing Neurofibroma in A Male 18-Year-Old Patient: A Case Report - Arissaputra, Sofyan; Abidin, Zainal (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p022, 2024)
Background : Neurofibromas are benign tumors originating from peripheral nervous system. While generally asymptomatic, they can cause significant morbidity, stigmatizing, and cosmetic concerns, requiring surgical intervention. This case report presents an interesting case of progressively enlarged and regrowing neurofibroma, which provides insights into the clinical aspect and treatment options in unusual cases. Case : An 18-year-old male patient presented with a progressively enlarging mass on his left dorsal pedis that had been present for eight years. The mass was soft, solitary, painless, accompanied by numbness, tingling, and a heavy sensation, occasionally causing difficult ambulatory. He was diagnosed with a neurofibroma and underwent wide surgical excision at another hospital. Physical examination revealed a well-defined mass measuring 12 x 7 x 5 cm, with hyperpigmentation and intact skin. Additional cutaneous lesions and café-au-lait spots suggested multiple neurofibromas, raising suspicion of Von Recklinghausen disease (neurofibromatosis type 1). Intraoperative findings confirmed a well-circumscribed, encapsulated tumor, which was completely removed by wide excision. A histopathological examination confirmed the diagnosis. The patient recovered well postoperatively, and a three-month follow-up showed no recurrence or neurological deficits. Conclusion: Neurofibromatosis type 1 can cause various manifestations, including progressive and regrowing large neurofibromas. Early detection and prompt surgical intervention are essential for preventing complications.